2002
DOI: 10.1073/pnas.082695299
|View full text |Cite
|
Sign up to set email alerts
|

A nonsense mutation in zebrafish gata1 causes the bloodless phenotype in vlad tepes

Abstract: Vlad tepes (vlt m651 ) is one of only five ''bloodless'' zebrafish mutants isolated through large-scale chemical mutagenesis screening. It is characterized by a severe reduction in blood cell progenitors and few or no blood cells at the onset of circulation. We now report characterization of the mutant phenotype and the identification of the gene mutated in vlt m651 . Embryos homozygous for the vlt m651 mutation had normal expression of hematopoietic stem cell markers through 24 h postfertilization, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
145
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(150 citation statements)
references
References 43 publications
3
145
0
Order By: Relevance
“…For genotyping lsd1 it627 , genomic DNA at the mutation sites was amplified by PCR using the primers 5′-ctggcagaggagggacaaactgcacggccggcggcagct and 5′-gcagtcatctgactgtgcg, and was digested with PvuII. Genotyping of gata1 m651 was carried out as described previously (16). Tranylcypromine was purchased from Enzo Life Sciences.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For genotyping lsd1 it627 , genomic DNA at the mutation sites was amplified by PCR using the primers 5′-ctggcagaggagggacaaactgcacggccggcggcagct and 5′-gcagtcatctgactgtgcg, and was digested with PvuII. Genotyping of gata1 m651 was carried out as described previously (16). Tranylcypromine was purchased from Enzo Life Sciences.…”
Section: Methodsmentioning
confidence: 99%
“…Gata1 encodes a transcription factor that transactivates a variety of erythropoietic genes. Gata1 gene KO mice and mutant zebrafish have been demonstrated to be lethally anemic because of drastic defects in erythropoiesis, and Gata1 has been considered to be a key factor required for erythropoiesis (14)(15)(16). Interestingly, the expression of Gata1 appears to define the hematopoietic commitment stage, because Gata1-positive cells display hematopoietic, but not endothelial, differentiation potential (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are both primitive and definitive waves of differentiation in the zebrafish, which produce primitive erythrocytes and macrophages, followed by definitive erthyrocytes, B cells, T cells, monocytes, granulocytes, and thrombocytes, respectively (Orkin and Zon, 1997;Trede and Zon, 1998;Herbomel et al, 1999;Willett et al, 1999;Bennett et al, 2001;Lieschke et al, 2001). Many zebrafish orthologs of blood-specific genes demonstrated to be important in mouse and human development have been isolated, including cmyb, gata1, gata2, globin, hhex, ikaros, lmo2, pu1, rag1, runx1, scl, and vegf (Hansen et al, 1997;Willett et al, 1997;Gering et al, 1998;Liao et al, 2000a;Liang et al, 2001;Burns et al, 2002;Lyons et al, 2002;Brownlie et al, 2003). Although the genetic program appears to be highly conserved during hematopoietic development in the vertebrate embryo, the site of hematopoiesis is not as consistent.…”
Section: Models Of Human Disease: Blood Disordersmentioning
confidence: 99%
“…In addition, this region is phylogenetically conserved in the human and mouse. On the contrary, it has been reported that the truncated type of GATA1 lacking the C-terminal region could not sustain erythropoiesis in zebrafish mutant Vlad tepes (27). A nonsense mutation at codon 339 in zebrafish GATA1 gene gave rise to massive deletion of GATA1 from the C-finger tail to the C terminus (Fig.…”
Section: C-terminal Region Is Vital For Transactivation Activity Of Gmentioning
confidence: 99%